2007
DOI: 10.1152/jn.00995.2006
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Facilitates a Persistent Calcium Current in Motoneurons of Rats With and Without Chronic Spinal Cord Injury

Abstract: facilitates a persistent calcium current in motoneurons of rats with and without chronic spinal cord injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
90
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(98 citation statements)
references
References 32 publications
7
90
1
Order By: Relevance
“…5-HT facilitates persistent inward current in spinal cord and vibrissa motoneurons (Cramer et al 2007;Li et al 2007) and it facilitates I NaP in mesencephalic and spinal motoneurons (Harvey et al 2006;Tanaka and Chandler 2006). In line with these reports we found that the induction of intrinsic spiking in spinal neurons by 5-HT goes in parallel with an increase in I NaP .…”
Section: -Ht Induces Intrinsic Spiking By Up-regulating I Nap Througsupporting
confidence: 88%
“…5-HT facilitates persistent inward current in spinal cord and vibrissa motoneurons (Cramer et al 2007;Li et al 2007) and it facilitates I NaP in mesencephalic and spinal motoneurons (Harvey et al 2006;Tanaka and Chandler 2006). In line with these reports we found that the induction of intrinsic spiking in spinal neurons by 5-HT goes in parallel with an increase in I NaP .…”
Section: -Ht Induces Intrinsic Spiking By Up-regulating I Nap Througsupporting
confidence: 88%
“…In addition, it also possible that there is more NaP in cells with less preserved descending input as a result of an adaptation to the lack of this synaptic or neuromodulatory input. For example, recent studies have shown that PICs in chronic SCI models become supersensitive to serotonin (Harvey et al 2006a;Li et al 2007) and norepinephrine (Rank et al 2007). In more complete injuries, it is possible that cells with an increase in the loss of descending input compensate more with a higher degree of supersensitivity adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…In most studies, neuromodulators are shown to facilitate PICs (Hounsgaard et al, 1988b;Li et al, 2007). In the in vitro sacrocaudal spinal cord preparation of adult rat, monoamine receptor antagonists inhibit sodium PICs (Harvey et al, 2006a,b), indicating the presence of an endogenous source of monoamines.…”
Section: Discussionmentioning
confidence: 99%